Effects of Sacha Inchi Tempeh on Oxidative Stress in Rats with Metabolic Syndrome - Afifah, Diana Nur; Nafisah; Anjani, Gemala; Syauqy, Ahmad; Mahati, Endang; Astawan, Made; Rahmawati, Irma Sarita (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2024)
Metabolic syndrome is a condition caused by metabolic disorders such as overweight, obesity, physical inactivity, and genetic factors. Increased reactive oxygen species (ROS) production in metabolic syndrome causes oxidative stress, characterized by decreased antioxidant capacity, increased malondialdehyde (MDA), and decreased superoxide dismutase (SOD) enzymes. Sacha inchi has a high alpha-linolenic acid (ALA) content, tocopherols, and antioxidants that can help protect liver tissue from damage caused by oxidative stress in metabolic syndrome. This study aimed to evaluate how sacha inchi tempeh affects the levels of MDA, SOD enzyme, and total antioxidant capacity (TAC) in Wistar rats with metabolic syndrome induced by a high-fat high-fructose diet (HFFD). The study used a true experimental pre-and post-control group design on rats with the intervention of sacha inchi tempeh (0.9 g, 1.8 g, 3.6 g) for 5 weeks (35 days). The ELISA (Enzyme-Linked Immunosorbent Assay) method with the FineTest procedure was used to measure levels of TAC, MDA, and SOD enzymes. The results of paired T-tests showed a significant difference in TAC levels before and after the intervention in the intervention group compared to the healthy group (p<0.05). MDA and SOD enzyme levels in rat liver tissue also improved significantly (p<0.05). Compared to simvastatin medication therapy, sacha inchi tempeh at a dose of 3.6 g had the best results. Therefore, sacha inchi tempeh is beneficial as a nutraceutical meal in reducing oxidative stress in individuals suffering from metabolic syndrome.